When Campylobacter jejuni affects the heart - myocarditis in male patients - Janiszewska, Michalina; Sobkowiak, Maciej; Sobkowiak, Paulina; Jusiak, Justyna; Łuczak, Janusz; Dżumaga, Justyna; Łuczak, Jeremi; Łazik, Maria; Dybowska, Roksana; Walaszek, Marta (Journal of Education, Health and Sport, 2026)
Introduction: Campylobacter jejuni is a bacteria that is one of the most common causes of bacterial foodborne illness worldwide. The bacteria is typically transmitted through consumption of undercooked poultry, contaminated water, or unpasteurized dairy products. In addition to gastrointestinal symptoms such as diarrhea, abdominal cramps or fever, C. jejuni has been associated with post-infection sequelae, including rare cases of myocarditis. Although uncommon, myocarditis can result in arrhythmias, heart failure or even death, requiring prompt medical attention. Methods: This review consists of the latest papers, including cases, systematic reviews and cohorts. The analysis focuses on summarizing the C. jejuni infection-related myocarditis in male patients, in particular determining the time of onset of gastrointestinal and cardiovascular symptoms, and the results of additional tests leading to the diagnosis of myocarditis. Results: Among the 46 reported male patients with Campylobacter jejuni-associated myocarditis or myopericarditis, left ventricular systolic dysfunction was documented in 17 cases (39.5%). The time interval between the onset of gastrointestinal symptoms and the onset of chest pain was available for 43 patients, with a mean delay of 3,84 days (median 3 days; range 0-14 days), indicating a short but clearly discernible latency between enteric infection and myocardial involvement. Overall, only one of the 46 patients (2.2%) died, whereas all others survived to hospital discharge, indicating a generally favourable short-term prognosis despite the relatively high proportion of cases with impaired ventricular function. Conclusions: Proper food handling, cooking poultry to appropriate temperatures, and good hygiene practices are essential for prevention of C. jejuni infections. Quick and precise diagnosis of myocarditis prevents severe complications of the disease.